Trustworthiness and Mobile banking Utilizations - Mohd. Hudzari, Haji Razali; Mohamad Noorman, Masrek; Normah, Omar (2013)
The main objective of this study is to investigate the relationship of between trustworthiness and mobile banking utilizations. Using a survey research methodology with questionnaire as the research instrument, data were collected from 312 mobile banking users in Malaysia. The results of the analysis showed that all the three components of trustworthiness namely, ability, integrity and benevolence were found to be positively related to mobile banking utilizations. The findings of this study will further enrich our understating on the topic of trust in the context of developing country such as Malaysia.